Preventing ureteric injury in total laparoscopic hysterectomy: a focus on surgical technique - Sarwar, Saeed; Khattak, Abubaker; Khattak, Noreen; Islam, Maria; Zarin, Mohammad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Hysterectomy is a frequently performed procedure in gynaecology. Laparoscopic hysterectomy offers the added advantages of reduced postoperative pain, minimal blood loss, shorter hospital stays, and lower incidence of surgical site infections. However, it does carry an elevated risk of injury to the urinary bladder and ureters. Recent technological advancements can help identify the ureters during laparoscopic hysterectomy, thereby decreasing the occurrence of lower urinary tract injuries. However, these advanced techniques are often not easily accessible in developing countries and can be expensive. We described a step-by-step approach to total laparoscopic hysterectomy that aims at minimising the risk of lower urinary tract injuries, and recent advances along with other methods to avoid urinary tract injuries are also discussed.